Reformulation of notary ethical supervision patterns in an effort to maintain the dignity of notary positions in Indonesia - Marcella Sacharissa Ali; Yos Johan Utama (IHSA Institute, 2026)
Notaries serve as public officials entrusted with producing authentic deeds that underpin legal certainty and sustain public confidence. Despite this mandate, breaches of ethics and professional obligations are still encountered in notarial practice, suggesting that the current scheme of ethical oversight has not operated effectively. In many instances, supervision emphasizes administrative compliance and tends to be complaint-driven, which limits its capacity to protect the dignity of the notarial office. This article examines both the legal framework and the practical application of notarial ethical supervision in Indonesia and formulates a redesigned oversight model oriented toward safeguarding the dignity of the profession. The study adopts a normative–empirical legal approach through statutory and conceptual review, supported by interviews and document analysis. The findings indicate a persistent gap between regulatory ideals and implementation, reflected in uneven supervisory practices, weak institutional coordination, and the lack of standardized indicators for ethical assessment. Accordingly, this study proposes an integrated and preventive supervision pattern to reinforce notarial professionalism and maintain public trust